Granulomatous Vasculitis and Persistent Measles Virus Infection in Crohn’s Disease - AJ Wakefield (Canadian Journal of Gastroenterology)
Based upon the recent observation of vasculitis in Crohn’s disease, a process that is more widespread than was recognized previously, the author investigated the possibility that this mechanism may provide an explanation for some of the clinical and histological idiosyncracies of this condition. In addition, it was suggested that the mesenteric microvascular endothelium may be a source of the persistent antigen that is responsible for ongoing cellular immunity in Crohn’s disease. This review discusses some of the studies designed to test these hypotheses, and discusses recent evidence for the presence of a measles-like virus in the endothelium in inflammatory foci, which may be relevant in the etiology of Crohn’s disease.